PENGARUH TERPAAN DRAMA KOREA TERHADAP PENGGUNAAN BAHASA KOREA PADA REMAJA DI KOTA DENPASAR - Kencana Putri, A.A. Putu Livia; Alit Suryawati, I Gusti Agung; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
Korean drama is one of the dramas on television that uses the Korean language, Korean dramas themselves are produced in South Korea with a miniseries format (16-20 episodes) with distinctive features that distinguish them from other series. The purpose of this study was to determine the effect of exposure to Korean dramas on the use of Korean in adolescents in Denpasar City. This study uses a quantitative research method in the form of an explanatory which has a casual nature. In this study also data collection using online questionnaire techniques via google form by taking 100 respondents. The results of this study are also positive, which means that the relationship between the two variables is unidirectional, which means that when exposure to Korean drama increases, the use of Korean in adolescents in Denpasar City is also getting better. Keywords: Korean Drama, Use of Korean Language, and, Uses and Effects Theory